2009
DOI: 10.1002/jor.20837
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt ions induce chemokine secretion in primary human osteoblasts

Abstract: Chemokines are major regulators of the inflammatory response and have been shown to play an important role in periprosthetic osteolysis. Titanium particles have previously been shown to induce IL-8 and MCP-1 secretion in osteoblasts. These chemokines result in the chemotaxis and activation of neutrophils and macrophages, respectively. Despite a resurgence in the use of cobalt-chromium-molybdenum alloys in metal-on-metal arthroplasty, cobalt and chromium ion toxicity in the periprosthetic area has been insuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 73 publications
3
58
0
Order By: Relevance
“…In vitro studies have demonstrated how higher cobalt ions concentrations inhibit primary human osteoblast and attract inflammatory and osteoclastic cells [13]. Elevated cobalt and chromium ions levels result in osteolytic reactions [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have demonstrated how higher cobalt ions concentrations inhibit primary human osteoblast and attract inflammatory and osteoclastic cells [13]. Elevated cobalt and chromium ions levels result in osteolytic reactions [12].…”
Section: Discussionmentioning
confidence: 99%
“…High cobalt and chromium concentrations have adverse effect on bone cells viability and osteoclast resorption [12,13]. Therefore, it should be logical to expect an increasing incidence of periprosthetic osteolysis around ASR implants of patients presenting high blood metal ion levels.…”
mentioning
confidence: 99%
“…MOM bearings made of a cobalt −chromium (CoCr) alloy generate a large amount of metal particles and ions in vivo [2]. Metal particles obtained from revisioned periprosthetic tissues were smaller than 50 nm, and the number of wear particles was 13-500 times higher than that seen in MOP bearings [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…The few studies investigating their role in bone formation show that peri‐prosthetic tissue cells produce factors that suppress osteoblast function and induce production of inflammatory cytokines 12, 13. Moreover, wear particles and metal ions can directly affect osteoblasts by reducing type one collagen production14, 15 and decreasing alkaline phosphatase activity as well as calcium deposition 16. In addition, wear particles have been shown to decrease osteoblast proliferation,15, 17 change the phenotype of mature osteoblasts,18 and stimulate osteoblasts to secrete inflammatory cytokines 14, 15, 16, 19.…”
mentioning
confidence: 99%
“…Moreover, wear particles and metal ions can directly affect osteoblasts by reducing type one collagen production14, 15 and decreasing alkaline phosphatase activity as well as calcium deposition 16. In addition, wear particles have been shown to decrease osteoblast proliferation,15, 17 change the phenotype of mature osteoblasts,18 and stimulate osteoblasts to secrete inflammatory cytokines 14, 15, 16, 19. Remarkably, one study revealed that cells from the peri‐prosthetic tissue produce several osteoblastic proteins themselves 20.…”
mentioning
confidence: 99%